Wertorientierungen - Ozil, Şeyda; Hofmann, Michael; Laut, Jens Peter; Dayıoğlu-Yücel, Yasemin; Zierau, Cornelia; Ucaq, Didem (Universitätsverlag Göttingen, 2022)
The contributions to this volume consider the meaning and treatment of values in literature, literary analysis, and advertising in the Turkish-German context. The work of Selim Özdoğan is strongly featured alongside examinations of texts by Emine Sevgi Özdamar, Deniz Utlu, and Cihan Acar. An excerpt from the English-language translation of Özdoğan's novel The Blacksmith's Daughter, a discussion between the author and translators, as well as reports and reviews round out the volume.